Implementation and Effectiveness of Risk Management for Organizing Umrah Worship in an Era of Global Economic Uncertainty: Case Study of Travel Maha Tour - Mutia Salwa Hutauruk; Ahmad Perdana Indra; Tuti Anggraini (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the implementation and effectiveness of risk management in organizing Umrah pilgrimage services amid global economic uncertainty through a case study of Travel Maha Tour. Global economic challenges, including exchange rate volatility, inflation, rising international transportation costs, and changes in cross-border policies, have significantly influenced the Umrah travel industry and increased operational risks. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and documentation. The informants consisted of the Operational Manager and Financial Manager of Travel Maha Tour, who were directly involved in managing operational and financial risks. Data were analyzed using descriptive techniques involving data reduction, data presentation, and conclusion drawing, while validity was ensured through source and method triangulation. The findings reveal that Travel Maha Tour has implemented comprehensive risk management by identifying key operational and financial risks, including currency fluctuations, flight schedule changes, visa delays, rising operational costs, and challenges related to pilgrims’ Umrah savings programs. To mitigate these risks, the company adopted several strategies, such as prudent budget management, reserve fund allocation, diversification of business partners, flexible payment policies, and strengthened internal communication and coordination. The implementation of these measures proved effective in maintaining service quality and operational sustainability. During the period of economic uncertainty from 2022 to 2024, Travel Maha Tour consistently fulfilled its departure quotas without imposing additional costs on pilgrims despite significant Rupiah exchange rate fluctuations. These findings indicate that effective risk management plays a crucial role in ensuring business resilience and protecting pilgrims’ financial interests during periods of global economic instability.